Influence of boron fertilization on cauliflower productivity, nutrient uptake and soil nutrient status in an acid Alfisol in Northwestern Himalaya. Issue 12 (4th July 2019) - Nazir, Gazala; Kumar, Pardeep; Shukla, Arvind K.; Sharma, Upinder
ABSTRACT: Modern agriculture over the years has resulted in depletion of boron (B) from soil which has been emerged as a serious obstacle for sustainable agriculture. We studied the availability of B in soil and cauliflower ( Brassica oleracea var. botrytis L.) productivity under different levels of B fertilization. A field experiment was conducted during 2013–2014 and 2014–2015, at experimental farm of Himachal Pradesh Agricultural University, Palampur on silt-clay loam soil (acid Alfisol) under mid hill wet temperate condition. Different levels of B for the study included 0, 0.75, 1.5, 2.5, 5, 10, 20 and 30 kg B ha −1 along with recommended dose (RD) of NPK and farmyard manure (FYM, 20 t ha −1 ). The application of B influenced biological yield significantly up to 5 kg ha −1 . Highest curd yield in 2013–2014 (11.03 t ha −1 ) and 2014–2015 (12.93 t ha − 1) was recorded in 1.5 and 0.75 kg ha −1 B along with NPK + FYM, respectively. At higher rates of boron i.e. 10, 20 and 30 kg ha −1, due to toxic effects, a reduction in curd yield was recorded in both years. Maximum mean uptake of N, P and K by leaves and curd was recorded with the application of boron at 1.5 kg ha −1, whereas mean B uptake was highest when boron was applied at 2.5 kg ha −1 . The highest mean value (1.79 mg kg −1 ) of soil available boron was recorded with 30 kg B ha −1 . Application of boron at 2.4 kg ha −1 was worked out as optimum dose for cauliflower.